PENGARUH BIAYA LINGKUNGAN DAN KINERJA LINGKUNGAN TERHADAP PROFITABILITAS PERUSAHAAN PEMENANG KATEGORI ISRA TAHUN 2018 - Amanda Oktariyani (Jurnal RATRI (Riset Akuntansi Tridinanti), 2020)
ABSTRACT This  study  aims  to  determine  the  influence  of  environmental  cost, firm  size proxied  by  total  asset  and  environmental  performance  proxied by environmental certification  of ISO 14001  on  the  operating  income  of  the  winners  in Indonesia  Sustainability  reporting  Awards  (ISRA)  2018. The  population  of  this  study is all the  winners  of  Indonesia Sustainability  Reporting  Awards  in  2018  and  they  have  reported  The  Sustainability  Report  for  three  years  from  2016  until  2018. The  result  show  that  environmental  cost  and  environmental performance  have  no influence  on  the  operating  income, while  firm  size has a  significant  influence on  the  operating  income. Simultanously, environmentalcost, firm size  and  environmental  performance  have  a  significant  influence  on the  operating  income.Keywords         :Environmental  Cost, Firm Size, Environmental  Performance, Operating Income, Indonesia  Sustainability  Reporting Awards, Sustainability  Report, Panel  Data  Regression